1974
DOI: 10.1172/jci107649
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Lithium-Induced Diabetes Insipidus in Man and the Rat

Abstract: A B S.T R A C T The mechanism of lithium-induced diabetes insipidus was investigated in 96 patients and in a rat model. Polydipsia was reported by 40% and polyuria (more than 3 liter/day) by 12% of patients receiving lithium. Maximum concentrating ability after dehydration and vasopressin was markedly impaired in 10 polyuric patients and was reduced in 7 of 10 nonpolyuric patients studied before and during lithium therapy. Severe polyuria (more than 6 liter/day) was unresponsive to trials of vasopressin and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
93
0
2

Year Published

1976
1976
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(101 citation statements)
references
References 35 publications
6
93
0
2
Order By: Relevance
“…Together, we believe that these and our mpkCCD cell line data strongly indicate that lithium-induced downregulation of AQP2 and thus lithium-induced NDI occur independent from adenylate cyclase activity. Our findings are in line with the finding that in rats that were treated for only 7 d with lithium, their lithium-induced polyuria was not interrupted by low doses of AVP but also not by cAMP (37).…”
Section: Lithium-induced Reduction Of Aqp2 Expression In Lithium-ndi supporting
confidence: 92%
“…Together, we believe that these and our mpkCCD cell line data strongly indicate that lithium-induced downregulation of AQP2 and thus lithium-induced NDI occur independent from adenylate cyclase activity. Our findings are in line with the finding that in rats that were treated for only 7 d with lithium, their lithium-induced polyuria was not interrupted by low doses of AVP but also not by cAMP (37).…”
Section: Lithium-induced Reduction Of Aqp2 Expression In Lithium-ndi supporting
confidence: 92%
“…The latter is well recognised in the literature (Thomsen, 1970;Singer et al, 1972;Forrest et al, 1974).…”
Section: Discussionmentioning
confidence: 84%
“…These subjects did not show polyuria. Similarly Forrest et al, (1974) found that all of the ten polyuric patients he studied had concentrating defects, but only seven of the ten non-polyuric patients had abnormal renal concentrating ability. Viol, Grof & Diagle (1975) found no evidence of renal concentrating defects in any of the ten patients receiving lithium whom they studied.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Lithium not only induces a vasopressin-resistant polyuria, i.e. nephrogenic diabetes insipidus (Singer et al, 1972;Forrest et al, 1974), but it also modulates the action of several hormones and neurotransmitters (Bakker., 1982;Newman et al, 1983;Waller et al, 1983). An elevated level of plasma corticosterone was observed in lithium-administered rats (Jacobs et al, 1978) and the stimulatory effect of lithium on ACTH secretion was suggested in vivo (Vatal et al, 1983) and in vitro (Zatz et al, 1985).…”
mentioning
confidence: 99%